TWO NEW TAXA OF ORNITHOBOEA (GESNERIACEAE) FROM THAILAND - Middleton, D. J.; Puglisi, C.; Suddee, S. (Edinburgh Journal of Botany, 2017)
The new species Ornithoboea grandiflora D.J. Middleton and new variety Ornithoboea maxwellii var. minutiflora D.J. Middleton are described.
Keywords: Limestone; Mae Hong Son; Tak